Uji Aktivitas Antibakteri Ekstrak Etanol Jamur Tiram Putih (Pleurotus ostreatus) - Annisa Ajeung Wulandari; Suwendar; Lanny Mulqie (Bandung Conference Series: Pharmacy, 2022)
Abstract. Infectious diseases are one of the biggest health problems causing death in the world, especially lower respiratory tract infections and diarrheal diseases. Infectious diseases can be caused by microorganisms that can weaken human health such as bacteria. One of the plants that can be used as an antibacterial is White Oyster Mushroom (Pleurotus ostreatus). This study aims to determine the antibacterial activity of the ethanol extract of white oyster mushroom, determination of the Minimum Inhibitory Concentration (MIC) and the working spectrum of the ethanol extract of white oyster mushroom. The results of this study showed that the ethanolic extract of white oyster mushroom did not produce the diameter of the inhibition zone on the growth of Staphylococcus aureus and Escherichia coli using the agar diffusion method at concentrations of 80%, 60%, 40%, 20% and 10%. MIC and working spectrum could not be determined because it did not inhibit the growth of Staphylococcus aureus and Escherichia coli using solid dilution method at concentrations of 80%, 40%, 20% and 10%. Abstrak. Penyakit infeksi adalah salah satu masalah kesehatan penyebab kematian terbesar di dunia terutama infeksi saluran pernapasan bawah dan penyakit diare. Penyakit infeksi dapat disebabkan oleh mikroorganisme yang dapat melemahkan kesehatan manusia seperti bakteri. Salah satu tanaman yang dapat dijadikan sebagai antibakteri yaitu Jamur Tiram Putih (Pleurotus ostreatus). Penelitian ini bertujuan untuk mengetahui aktivitas antibakteri dari ekstrak etanol jamur tiram putih, penetapan Konsentrasi Hambat Minimum (KHM) dan spektrum kerja dari ekstrak etanol jamur tiram putih. Hasil penelitian ini menunjukkan bahwa ekstrak etanol jamur tiram putih tidak menghasilkan diameter zona hambat pada pertumbuhan Staphylococcus aureus dan Escherichia coli menggunakan metode difusi agar pada konsentrasi 80%, 60%, 40%, 20% dan 10%. KHM dan spektrum kerja tidak dapat ditentukan karena tidak menghambat pertumbuhan Staphylococcus aureus dan Escherichia coli menggunakan metode dilusi padat pada konsentrasi 80%, 40%, 20% dan 10%.